Optimising maintenance cost performance with skilled technicians - Au-Yong, C.P.; Ali, A.S.; Ahmad, F. (Emerald, 2014)
Purpose – High-maintenance cost is the common issue in building industry due to low service quality of maintenance management in Malaysia. Lack of preventive measure is the problem that implicates poor maintenance performance. Scheduled maintenance is suggested to improve the maintenance performance. However, the effectiveness of scheduled maintenance can be greatly influenced by the availability of skilled technicians. Thus, the purpose of this paper is to identify the aspects of skilled technician to be concerned in maintenance management, as well as to establish the relationship between the aspects and maintenance cost performance.